Análise comparativa do isolamento acústico em diferentes geometrias: Ensaios em campo e simulações computacionais - Heissler, Rafael Ferreira (Universidade do Vale do Rio dos Sinos, 2018)
Currently in Brazil, building companies need to design and construct residential buildings with a minimum of acoustic insulation conditions, and to this end, the acoustic characteristics of the constructive system must be well known. For the design situation, sound insulation data of the systems tested in the laboratory are used as input values in computational simulations, and thus, to estimate the results that can be obtained in field tests. However, the requirements only contemplate the minimum results that the system must have when performed in the laboratory and verified in the field situation, not allowing the use of acoustic prediction methods to estimate the performance in design stages. This entails a need for total sampling of the building since requirements are established according to the kind of the units. Thus, this study aims to present results of the weighted standardized sound level difference and weighted standardized impact sound pressure level of different building systems tested in the same building, with a focus on comparative analysis of different areas and geometry and obtained from estimation of acoustic prediction software. The tests were carried out in residential buildings located in the region of Porto Alegre, according to the technical standards ISO 16283-1 and ISO 16283-2, and estimated with the use of software SONarchitect. An analysis of the uncertainty of measurement from a historical data series was carried out to verify if there is influence of the geometry in the expanded uncertainty. For the airborne condition, it was found that part of the tests presented shown results with a lower value than those found by means of the test, and the measurement uncertainty tends to be higher as the volume of the room tested increases. However, for the impact noise transmission tests, the estimated values were very close to the test results, however, it was not possible to relate the measurement uncertainty to the volume of the room tested.
Keywords: Acústica de edifícios; Desempenho de edificações; Incerteza de medição; Building acoustics; Dwelling performance; Measurement uncertainty; ACCNPQ::Ciências Sociais Aplicadas::Arquitetura e Urbanismo